Subcellular and Dynamic Coordination between Src Activity and Cell Protrusion in Microenvironment - Zhuo, Yue; Qian, Tongcheng; Wu, Yiqian; Seong, Jihye; Gong, Ya; Ma, Hongwei; Wang, Yingxiao; Lu, Shaoying (NATURE PUBLISHING GROUP, 2015)
Migration of endothelial cells is essential for wound healing and angiogenesis. Src kinase activity plays important roles at the protrusions of migrating endothelial cells. However, the spatiotemporal coordination between Src kinase activity and the protrusion of cell edge remains unclear. Therefore, we investigate these coordinated molecular events at the initiation of cell migration, by integrating microfabrication, fluorescence resonance energy transfer (FRET)-based biosensors, and automated computational image analysis. We demonstrate that the physical release of restrictive micropattern triggered a significant decrease of Src activity at the protrusive edge of endothelial cells. Computational cross-correlation analysis reveals that the decrease of Src activity occurred earlier in time, and was well-coordinated with the protrusion of cell edge in polarized cells, but not in non-polarized cells. These results suggest that the spatiotemporal control of Src kinase activity is well-coordinated with cell polarization and protrusion in endothelial cells upon the release of physical constraint, as that experienced by endothelial cells sprouting from stiff tumor micro-environment during angiogenesis. Therefore, our integrative approach enabled the discovery of a new model where Src is de-activated in coordination with membrane protrusion, providing important insights into the regulation of endothelial migration and angiogenesis.
Keywords: FOCAL ADHESION KINASE; GEOMETRIC CONTROL; ACTIN-FILAMENTS; ANGIOGENESIS; MEMBRANE; ACTIVATION; MIGRATION; STIFFNESS; PROTEINS; GROWTH